Medical Journal of Shree Birendra Hospital: Journey Continues. - Joshi, Amit (Medical Journal of Shree Birendra Hospital, 2013)
Medical Journal of Shree Birendra Hospital; Jan-June 2012/vol.11/Issue1/1-3 DOI: http://dx.doi.org/10.3126/mjsbh.v11i1.7757